AKULTURASI ISLAM JAWA DALAM TRADISI NYUMBANG MANTU (Studi Kasus Masyarakat Wates Semarang dengan Pendekatan Antropologi Dakwah) - Safrodin Safrodin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2017)
This study aims to explain one of the embodiment of acculturation of Islamic and Javanese culture in the tradition of mantu and nyumbang mantu on Javanese society at Wates Semarang with anthropological perspective. Mantu in the tradition of the Javanese society includes mantu khitanan and mantu ngantenan. It has an important meaning in the eyes of the people. In addition to the cultural demands, in it also has the meaning of religion, custom and meaning of prestige for them, so that as much as possible they will hold a mantu though must with gotong royong. Gotong royong has long been formed in the tradition of nyumbang mantu. This tradition of nyumbang mantu is a manifestation of brotherhood and solidarity in society, as well as a social obligation accompanied by other expectations such as social prestige, social dignity and blessings. The nyumbang mantu is also a manifestation of the ta'āwun principle in a society that has been institutionalized in tradition and culture. On the other hand, the transformation of mantu from simple slametan to walīmah, which is accompanied by religious teachings [pengajian] of mantenan and religious entertainment, especially in santri society, is actually a form of acculturation of Java and Islam. This acculturation occurs as a process of strengthening to the Islamic values in society. Because, the certain values that society believes will only survive when it grows and develops into a culture in society.